TRANSNATIONAL CORPORATIONS AND THE NIGERIAN ECONOMY IN THE 21ST CENTURY: ARE THEY TWO SIDES OF A COIN? - Igbani, Robbins Owede; Inegite, Godknows Livingston (African Journal of Social and Behavioural Sciences, 2025)
This study explored the complex relationship between Transnational Corporations (TNCs) and the Nigerian economy, posing the critical question of whether their activities represent two sides of the same coin. The study made use of qualitative research design in both data collection and analysis. The study specifically examines the contributions of TNCs like Shell, Chevron Nigeria Ltd., MTN Group Ltd. etc. The findings revealed that the origin and growth of Transnational Corporations date back to the era of the European Trading companies in Africa and Asia, such as the Dutch East Indian Trading Company, the Royal Niger Company, British South African company. The study also revealed that TNCs, specifically in the oil and gas sector are indeed two sides of a coin, as their activities and impacts are both negative and positive. The positive part is that TNCs are the movers and shakers of the Nigerian economy as they remained the most significant facilitators of FDI and revenue to the Nigerian economy in sectors like ICT, oil and gas, rail and road construction, finance etc. Thus, for example, between 2022 and 2023 alone, the SPDC and SNEPCo paid a combined 1.09 billion and 1.36 billion dollars as corporate taxes and royalties to the Nigeria government, aside from Corporate Social Responsibilities (CSR), in their operational areas. Again, between 2021-2023 alone, Chevron Nigeria Ltd. paid over 3.4 billion as corporate tax and royalties to the Nigerian government. The signing of the China Belt and roads initiative in 2018 by Nigeria has also attracted Chinese state own corporations to construct the Lekki Deep Sea port, Zungeru Hydroelectric project, Lagos-Ibadan train route construction of airport terminals and ports etc. On the contrary, the UNEP report affirmed that the activities of the IOCs have polluted Ogoni land and other oil-producing communities in the Niger Delta and have impacted negatively on the ground, water, soil, terrestrial and aquatic vegetation and public health such that it will take an average of 25 to 30 years to restore the environment arising from oil pollution and gas flare in the region. The Chinese state-owned Corporations have also been found committing grievous human rights violations against Nigerians, specifically during the COVID-19 pandemic.